Pre-Service Kindergarten Teachers’ Confidence and Beliefs in Music Education: A Study in the Chinese Context - Siu-Hang Kong; Xiaoyu Xiong (Education Sciences)
Generalist kindergarten teachers often report insufficient theoretical and pedagogical preparation for music instruction in their teacher education, leaving them feeling underprepared. This study explores how pre-service kindergarten teachers in Hong Kong perceive their confidence in teaching music and how this perception influences their beliefs about the importance of music education. A total of 467 first-year pre-service teachers completed a questionnaire assessing their self-confidence in conducting music activities and their beliefs regarding the importance of music education for young children. Results showed that participants exhibited the lowest confidence in music teaching compared to other learning areas, particularly in activities requiring specialised musical knowledge and creativity, such as instrumental performance and music creation. A significant positive correlation was found between teachers’ perceived confidence and their belief in the importance of music education (rs(465) = 0.39, p < 0.001). These findings may offer insights into the influence of cultural values on their teaching belief. This study highlights the need for culturally responsive teacher education programmes that address the specific challenges faced by generalist teachers in early childhood music education within Hong Kong and broader Chinese educational contexts.